(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the technology of sodium hydroxide roasting and hydrometallurgical processing for extracting manganese from metallurgical slags. The study tested methods for obtaining a selective solution from slag samples roasted at temperatures of 200°C and 300°C using distilled water and 16% sulfuric acid. Based on EDXRF and XRD analyses, manganese compounds with a purity of up to 34% were isolated, and the ecological and economic advantages of this method were substantiated.